Interlaboratory Reliability of Microimmunofluorescence Test for Measurement of Chlamydia pneumoniae-Specific Immunoglobulin A and G Antibody Titers - Littman, Alyson J. (American Society for Microbiology, 2004)
To evaluate the reliability of Chlamydia pneumoniae-specific immunoglobulin G (IgG) and IgA antibody titers as measured by the microimmunofluorescence (MIF) test, we compared results from 392 individuals using a standard MIF protocol at two academic laboratories. The kappas for dichotomous titers (≥16 versus <16) were 0.39 for IgA and 0.53 for IgG. Measurement error likely attenuates C. pneumoniae-disease associations; the magnitude of attenuation can be estimated from results of studies such as this one.